Osnovy teorii sportivnych sorevnovanij v sisteme nauk o sporte - Krasnikov, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The author proves the urgency of inclusion of the discipline, integrating the didactically arranged information on the problems arising in connection with the direct participation of sportsmen in competitions, in the training plan of the specialists focused on the sports of maximum achievements. The structure of the subject matter "Basis of the theory of sports competitions" is submitted according to the program and the manual developed by the author.